Nanotechnology for environmental remediation - Joo, Sung Hee.; Cheng, I. Francis (New York : Springer, 2010)
This book provides information on newly discovered chemical process, which could revolutionize the treatment of pesticides and contaminated water.
Literature Review.- Nanoscale ZVI Particles Manufacture and Analytical Techniques.- Oxidative Degradation of the Thiocarbamate Herbicide, Molinate, Using Nanoscale ZVI.- Molecular Oxygen Activation by FeII/IIIEDTA as a Form of Green Oxidation Chemistry.- Quantification of the Oxidizing Capacity of Nanoparticulate Zero-Valent Iron and Assessment of Possible Environmental Applications.- Conclusions and Future Research Needs.
Includes bibliographical references.
Keywords: MODERN INORGANIC CHEMISTRY